LRRK2-phosphorylated Rab10 sequesters Myosin Va with RILPL2 during ciliogenesis blockade - Dhekne, Herschel S (Life Sci Alliance, 2021)
Activating mutations in LRRK2 kinase causes Parkinson’s disease. Pathogenic LRRK2 phosphorylates a subset of Rab GTPases and blocks ciliogenesis. Thus, defining novel phospho-Rab interacting partners is critical to our understanding of the molecular basis of LRRK2 pathogenesis. RILPL2 binds with strong preference to LRRK2-phosphorylated Rab8A and Rab10. RILPL2 is a binding partner of the motor protein and Rab effector, Myosin Va. We show here that the globular tail domain of Myosin Va also contains a high affinity binding site for LRRK2-phosphorylated Rab10. In the presence of pathogenic LRRK2, RILPL2 and MyoVa relocalize to the peri-centriolar region in a phosphoRab10-dependent manner. PhosphoRab10 retains Myosin Va over pericentriolar membranes as determined by fluorescence loss in photobleaching microscopy. Without pathogenic LRRK2, RILPL2 is not essential for ciliogenesis but RILPL2 over-expression blocks ciliogenesis in RPE cells independent of tau tubulin kinase recruitment to the mother centriole. These experiments show that LRRK2 generated-phosphoRab10 dramatically redistributes a significant fraction of Myosin Va and RILPL2 to the mother centriole in a manner that likely interferes with Myosin Va’s role in ciliogenesis.